Penggunaan Kekerasan Sebagai Cara Memperoleh Wilayah Bertentangan Dengan Hukum Internasional - Damura, Fahira Ode; Anwar, Arman; Tahamata, Lucia Charlota Octovina (Faculty of Law, Universitas Pattimura, 2021)
Introduction: The territorial sovereignty of a country includes three dimensions, namely land, air and sea.Purposes of the Research: The purpose and benefit of this research is to demonstrate the study and analysis of the rules of territorial control and international law.Methods of the Research: The type of research used in this research is normative law which is sourced from primary and secondary legal materials whose data is collected through library research.Results of the Research: Based on the results of the research, it shows that the regulation of territorial control is regulated in international law but is prohibited if it is carried out by means of violence as stipulated in the UN Charter Article 2 paragraphs (3) and (4). The form of territorial conquest is currently strictly prohibited, this is emphasized in UN Security Council resolution 242 concerning the illegality of territorial control by war. The use of violence is only allowed in terms of self-defense, or based on the mandate of the UN Security Council for humanitarian purposes (humanitarian intervention). Apart from the above, in both classical international law and customary international law, the use of force and subjugation has not yet reached the stage of being prohibited.